Water column raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM64 - Dagmar Kieke; Christian dos Santos Ferreira; Laura Frahm; Andrea Gerriets; Asmund Herland; Gard Stokland (PANGAEA, 2022)
Water column raw data using the ship extquotesingles own Kongsberg EM 122 multibeam echosounder was not continuously recorded during RV MARIA S. MERIAN cruise MSM64. Data was recorded on 2 days between 2017-05-30 and 2017-05-31 to re-calibrate the system. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH and added to the corresponding multibeam raw dataset https://doi.org/10.1594/PANGAEA.944237 This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM).